PKM. SDN APUAN BANGLI DALAM PENGEMBANGAN KEMAHIRAN MENGAJAR GURU MATEMATIKA DI SEKOLAH DASAR UNTUK PENINGKATAN PROFESIONAL GURU - I Wayan Muliana; I Komang Sukendra; I Wayan Sumandya (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2023)
Professional teachers are teachers who are able to meet competency standards and are proven by professional certificates. Elementary school teachers are class teachers whose duties are required to master many subjects. Therefore, it is undeniable that the mastery of knowledge (material) in several subjects is not optimal and there is the potential for errors or misconceptions to occur in learning mathematics. There are indications that elementary school teachers lack mastery of the material and are less proficient in learning mathematics. Inadequacy in learning Mathematics is a factor of teacher weakness and hinders the achievement of learning objectives, as well as influencing students' positive disposition towards Mathematics. In order to overcome errors or misconceptions in learning mathematics in elementary schools, each teacher must improve teaching skills by understanding mathematical concepts and principles correctly so that the teacher's knowledge increases and the teacher can change the way he teaches in class. Teacher teaching skills can be improved through workshop activities. Teaching skills development is an effective and structured professional development that results in changes to teachers' knowledge and practice in learning mathematics. Conceptually, teaching proficiency is a product of activities embedded in work. In-learning activities supported by teaching skills enhance teachers' knowledge and help them change the way learning is taught in the classroom. Formally developing teaching skills is part of the range of experiences that can result in professional learning